A Green Advertising Wuling on Purchase Intention Mediated by Perceived Value and Attitude - Yumna, Atika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to identify the effect of green advertising on the purchase intention of Wuling consumers, with green perceived value and green product attitude as mediating variables. This study uses the explanatory type to explain the relationship between dependent and independent variables. The sample in this research consisted of 105 respondents from the population of Wuling brand consumers in Surabaya City, selected using the probability sampling method. The data analysis was conducted using SmartPLS 3. The results show that green advertising does not have a significant direct effect on purchase intention. However, green advertising has a significant effect on green perceived value and green product attitude, which in turn positively affects purchase intention. Based on these findings, it can be concluded that green advertising can indirectly influence purchase intention through green perceived value and green product attitude.